The Effect of Covid-19 Pandemic on the Performance of Islamic Bank in Indonesia - Sutrisno, Sutrisno; Panuntun, Bagus; Adristi, Fikri Irfan (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2020)
The Corona Virus Diseases (Covid-19) pandemic that hit the world resulted in a decline in the performance of most companies, including reducing the performance of the world economy. The pandemic has changed human behavior so that it needs adaptation to new habits. Banking as a business group was also affected because the decline in company performance had an effect on the decline in banks, including Islamic banks. The purpose of this study is to examine the impact of the Covid-19 pandemic on the performance of Islamic banks in Indonesia. The performance of Islamic bank consist of capital adequacy ratio (CAR), non-performing financing (NPF), profitability as measured by return on assets (ROA), return on equity (ROE), and net operating margin (NOM)., operating expenses to operating income ratio (OEIR) and financing to deposit ratio (FDR). The population in this study were 13 Islamic commercial banks operating in Indonesia. From this population 12 banks were taken as samples and one bank was not taken because the data were incomplete. The data is taken quarterly, namely 4 quarters before the pandemic and 3 quarters during the pandemic. To test the hypothesis, the independent sample t-test was used. The results showed that the profitability as measured by ROE and NOM has a significant effect, as well as the financing to deposit ratio is also significantly different. Meanwhile, CAR, NPF, ROA, and OEIR were not affected by the Covid-19 pandemic